Pengaruh Efektivitas Kerja dan Pendapatan terhadap Tingkat Kesejahteraan Kelompok Wanita Tani (KWT) Kecamatan X Koto Singkarak - Ghina Jannatul Hamidah; Esi Sriyanti; Afni Yeni (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This quantitative study, involving 135 respondents, aims to analyze the influence of work efficiency and income on the welfare level of members of the Women Farmer Group (KWT) in X Koto Singkarak Sub-district. Data were collected through structured questionnaires and analyzed using multiple linear regression, t-tests, and F-tests to determine both partial and simultaneous effects of the independent variables on welfare. The results of the t-test reveal that work efficiency (X1) does not have a significant partial effect on the welfare of KWT members (Y), as indicated by a t-value of -1.817, which is lower than the t-table value of 1.977, and a significance level of 0.071, which exceeds 0.05. Conversely, income (X2) demonstrates a strong and significant partial effect on welfare, supported by a significance value of 0.000, which is lower than 0.05, and a t-value of 13.561, which is higher than the t-table value of 1.977. Furthermore, the simultaneous F-test confirms that work efficiency and income collectively have a significant effect on the welfare level of KWT members, with an F-value of 98.319 exceeding the F-table value of 19.490 and a significance level of 0.000. These findings indicate that increasing income plays an important role in improving welfare.